STRATEGI BERSAING RUMAH MAKAN HENI PUTRI KAILI - Raymondo Wengkau; Chalil Chalil; Maskuri Maskuri (Universitas Tadulako, 2015)
Heni Putri Kaili Restaurant is located at Kaombona Street/ Kampung Nelayan No. 09 Talise, East Palu Sub-district, Palu City. Heni Putri Kaili restaurant has been established since 6 years ago, precisely on February 20th 2010. The owner of the restaurant is Mrs. Haeni R. Kara , S.Pd. The research intends to find out the competitive level faced by Heni Putri Kaili Restaurant among the restaurant industries in Palu City and to comprehend the alternative strategy that can be used by Heni Putri Kaili Restaurant. Data analysis methods used are Porter’s Five Forces analysis and the SWOT (Strength, Weakness, Opportunities, Threats) analysis. Based on Porter’s Five Forces analysis, the study concludes that Heni Putri Kaili restaurant experiences a great rivalry among the restaurant industries in Palu City, which includes the rivalry beetween the competitors from the similiar industry, the suplier’s supplying capacity, and the threat of substitutes products. The result of SWOT metric diagram and IE table suggests that Heni Putri Kaili Restaurant should focus on the diversifications strategy while improving the service and the strategy to increase the promotion of the main product together with other products that are still unfamiliar by the consumers/markets. Heni Putri Kaili Restaurant terletak di Kampung Nelayan No. 09 Talise, Kecamatan Palu Timur, Kota Palu. Restoran Heni Putri Kaili telah berdiri sejak 6 tahun yang lalu, tepatnya pada 20 Februari 2010. Pemilik restoran tersebut adalah Nyonya Haeni R. Kara, S.Pd. Tujuan penelitian ini adalah untuk mengetahui kondisi persaingan restoran Heni Putri Kaili di antara industri restoran di Kota Palu dan untuk mengetahui strategi alternatif yang dapat digunakan oleh restoran Heni Putri Kaili. Metode analisis data yang digunakan adalah analisis Lima Kekuatan Porter dan SWOT (Strength, Weakness, Opportunities, Threats). Berdasarkan analisis Lima Kekuatan Porter, dapat disimpulkan bahwa persaingan antara restoran Heni Putri Kaili di industri restoran di Kota Palu mengalami persaingan yang sangat baik. Ada banyak faktor; persaingan antara pesaing dari industri serupa, kapasitas penyuplai suplier, dan ancaman produk substitusi. Sebagai hasil diagram metrik SWOT dan tabel IE, strategi kompetitif dapat direkomendasikan. Restoran Heni Putri Kaili berfokus pada Strategi Diversifikasi dengan program strategi untuk menegakkan dan memperbaiki layanan dan strategi untuk meningkatkan promosi produk unggulan tanpa meninggalkan produk lain yang masih belum diketahui oleh konsumen / pasar.